The Result of Continuous Antibiotics Injection in Out Patient, Sawanpracharak Hospital - Aungsathammarat, Aunchalee; Dejpun, Budsaya (Srinagarind Medical Journal, 2021)
Background and Objective: Increasing the use of outpatient intravenous antibiotic therapy and Outpatient parenteral antimicrobial therapy (OPAT) program have been developed standardization in many country. Objective of this research is to assess the effects of continuous antibiotic injection in the treatment of infectious diseases in outpatients who receiving medicine at Sawanpracharak Hospital Methods: The descriptive study was performed in 529 outpatients receiving antibiotic injection between 1 October 2019 to 30 September 2020. Results: According to the study, 616 episodes OPAT for 529 patients were prescribed. The department which was the highest amount of prescribing was internal medicine (289 episodes, 46.90 %). The most commonly prescribed drug was ceftriaxone 426 episodes (67.73%). The most infectious disease was urinary tract infections 228 episodes (37.01%). There were 318 patients ( 51.62%) using an outpatient injection service at Sawanpracharak Hospital. The most drug related problem prescription error was that the type of solution and the dose rate of administration was not specified 98.92%. Treatment outcomes were clinical improvement by 90.90% and 4.06% of patients had to admit in hospital for treatment infection. There were adverse drug event 3 cases and none-compliance 18 cases. Conclusion: Outcomes of The continuous antibiotic injection in outpatients. there was clinical improvement 90.90 % can reduce length of stay and also reduce the cost of hospital stay by more than 2.5 million bahts per year. Orientation for referring to patients by pharmacists. There were adverse drug event 3 cases and none-compliance 2.92%.